A Visualization-based Approach for the TaxonomyBrowser Interface - Rey, Marina Fortes Rey; Freitas, Carla Maria Dal Sasso Freitas (Teste; 2018: IHC_21, 2018)
The process of collecting biological data is a continuous activity, specially in field work for research projects or teaching activities. Data obtained from these collecting activities need to be properly stored in order to be readily available for future analysis. TaxonomyBrowser is a biodiversity information system mainly developed to manage data collected by biologists during field work. It stores such data on a database organized according the taxonomic tree of leaving species. This work describes a new approach for the TaxonomyBrowser's user interface, focusing on providing an easier and more intuitive method of managing and visualizing the information stored in such databases. The approach was assessed by means of a survey conducted with users from the field of study as well as users with no knowledge on biodiversity information systems. The participants considered the application to be good and mostly provided positive feedback.